Calcilytic NPS 2143 Reduces Amyloid Secretion and Increases sAβPPα Release from PSEN1 Mutant iPSC-Derived Neurons - Lo Giudice, Maria; Mihalik, Balázs; Turi, Zsófia; Dinnyés, András; Kobolák, Julianna (Journal of Alzheimer's disease, 2019)
Despite numerous efforts and studies over the last three decades, Alzheimer’s disease (AD) remains a disorder not fully understood and incurable so far. Development of induced pluripotent stem cell (iPSC) technology to obtain terminally differentiated neurons from adult somatic cells revolutionized the study of AD, providing a powerful tool for modelling the disease and for screening candidate drugs. Indeed, iPSC reprogramming allowed generation of neurons from both sporadic and familial AD patients with the promise to recapitulate the early pathological mechanisms in vitro and to identify novel targets. Interestingly, NPS 2143, a negative allosteric modulator of the calcium sensing receptor, has been indicated as a possible therapeutic for AD. In the present study, we assessed the potential of our iPSC-based familial AD cellular model as a platform for drug testing. We found that iPSC-derived neurons respond to treatment with γ-secretase inhibitor, modifying the physiological amyloid-β protein precursor (AβPP) processing and amyloid-β (Aβ) secretion. Moreover, we demonstrated the expression of calcium sensing receptor (CaSR) protein in human neurons derived from healthy and familial AD subjects. Finally, we showed that calcilytic NPS 2143 induced a changing of Aβ and sAβPPα secreted into conditioned media and modulation of CaSR and PSEN1 expression at the plasma membrane of AD neurons. Overall, our findings suggest that NPS 2143 affects important AD processes in a relevant in vitro system of familial AD.